Avaliação da suportabilidade dielétrica do isolamento em ar e coordenação de isolamento de linhas de transmissão - Reis, Arthur Linhares Esteves dos (2018)
This dissertation analyzes the dielectric strength of phase-to-ground and phaseto-phase clearances of overhead transmission lines (TL) and the impact of its computation methodology on the design of these lines. From the results of laboratory tests for typical configurations, the equations traditionally used to determine the critical flashover voltage for switching surges have been developed over the years. However, it is known that this critical voltage depends on the shape of the electrodes and the electric field distribution along the gap, restricting their application with precision to the new geometric conceptions of TL. Therefore, initially in this dissertation, the feasibility of alternative methods was investigated, implementing more generic solutions for the computation of the dielectric strength of lines with conventional and non-conventional bundles. An important result was the development of a new computational methodology to aid in the process of insulation coordination, a fundamental stage of the TL design. In this methodology, the dimensions of the tower are defined according to the maximum risk of failure, by a statistical method of insulation coordination. With its application, implemented in the CISOL software, a sensitivity analysis of the influence in the TL design of some parameters was performed. Among the obtained results, it was observed that for TL with optimized electric field distribution on the conductors’ surface, the adoption of more precise methodologies for the insulation coordination, as the one developed here, indicates an even greater reduction in the tower distances, and consequently, further enhancement of the line design. Thus, it is possible to minimize the costs and environmental impacts of the lines, as well as to improve their electrical performance in the system.